PENGAWASAN LINGKUNGAN HIDUP DI KABUPATEN KUANTAN SINGINGI (KASUS PERTAMBANGAN EMAS TANPA IZIN (PETI)) - Melki Harisandi; Zaili Rusli, SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Unlicensed gold mining is still a big problem in Kuantan Singingi district. Kuantan Singingi Regency Government has established an Integrated Team for the implementation of illegal mining supervision and control (PETI). Despite having a special team to deal with the problem, unauthorized gold mining still exists today.The research is done to know how the implementation of unauthorized gold mining supervision and to know what factors affect the supervision of gold mining without permission in Kuantan Singingi Regency. According to the theory there are several types and supervision techniques that need to be applied in the implementation of surveillance, which researchers use is refresive supervision with indicators set the measuring tool (standard), perform assessment actions, and take corrective action. This research uses descriptive qualitative method that is analysis which try to give detailed description based on reality found in field.The results of this study indicate that the implementation of unauthorized gold mining supervision in Kuantan Singingi regency conducted by the Integrated enforcement team of PETI Kuantan Singingi has not been successful. There are some shortcomings such as the adoption of standards, taking assessment actions, and remedial actions have not run maximally. This is because there are several factors that influence the implementation of such supervision.Keywords : Gold Mining, Suvervising, Integrated Team